Synthesis of Diarylmethanes by Cobalt-Catalyzed Reductive Cross-Coupling via Csp3–S Bond Activation - Gao, M.-Y.; Durandetti, M.; Gosmini, C. (Synthesis, 2025)
Various diarylmethane derivatives were synthesized by cobalt-catalyzed cross-electrophilic coupling of benzylsulfonium salts with various aryl bromides in moderate to good yields. This simple protocol exhibited good tolerance for various functional groups. We demonstrated that low-valent cobalt was able to activate both aryl halides and C–S bonds from stable benzyl sulfonium salts, readily available from alcohols. Preliminary mechanistic studies suggested the involvement of benzyl radicals generated from C–S bond cleavage through a single electron transfer.
Keywords: Cross-coupling; Cobalt; Sulfonium salt; Diarylmethane; Benzyl radical